Stable Isotope Analysis Reveals Detrital Resource Base Sources of the Tree Hole Mosquito, Aedes triseriatus - Kaufman, Michael G. (2010)
1. Detritus that forms the basis for mosquito production in tree hole ecosystems can vary in type and timing of input. We investigated the contributions of plant- and animal-derived detritus to the biomass of Aedes triseriatus (Say) pupae and adults by using stable isotope ((15)N and (13)C) techniques in lab experiments and field collections. 2. Lab-reared mosquito isotope values reflected their detrital resource base, providing a clear distinction between mosquitoes reared on plant or animal detritus. 3. Isotope values from field-collected pupae were intermediate between what would be expected if a single (either plant or animal) detrital source dominated the resource base. However, mosquito isotope values clustered most closely with plant-derived values, and a mixed feeding model analysis indicated tree floral parts contributed approximately 80% of mosquito biomass. The mixed model also indicated that animal detritus contributed approximately 30% of mosquito tissue nitrogen. 4. Pupae collected later in the season generally had isotope values that were consistent with an increased contribution from animal detritus, suggesting this resource became more nutritionally important for mosquitoes as plant inputs declined over the summer.